The effect of monosaccharide reducing sugars on the atom transfer radical polymerization of n-butyl methacrylate and methyl methacrylate - De Vries, Andrew Robert (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2001